Membangun Teologi Ekologi dari Tradisi Memindahkan Hujan Masyarakat Halmahera - Marthen Dominggus Boediman; Ebin Eyzer Danius (Sekolah Tinggi Teologi SAPPI Ciranjang, 2026)
This study explores the potential of the rain-shifting tradition of the Halmahera people as a source for developing a contextual ecotheology within the Evangelical Christian Church in Halmahera. Using a descriptive qualitative approach, data were collected through in-depth interviews with customary leaders, church leaders, and community members, observations of cultural practices, and a review of literature on local cosmology and ecological theology. The findings show that the rain-shifting practice reflects an ecological understanding of the interconnectedness of humans, nature, and the Divine, while emphasizing human responsibility for maintaining the balance of creation. Ritual symbols used in the practice represent local perceptions of cosmic harmony and environmental stewardship. This tradition provides valuable resources for theological reflection and the development of a contextual ecotheology in Halmahera. The study therefore recommends integrating these ecological values into GMIH’s theological reflection and praxis to strengthen ecological awareness amid contemporary environmental challenges.